Euthanasia : opposing viewpoints - Wekesser, Carol, 1963- (San Diego : Greenhaven, 1995)
Presents a wide diversity of opinions on euthanasia, and includes discussions on ethics, legalization, physician-assisted suicide, decisions, and infant euthanasia.
Is euthanasia ethical? -- Should euthanasia be legalized? -- Should physicians assist in euthanasia? -- Who should make decisions about euthanasia? -- Is infant euthanasia ethical?
Includes bibliographical references and index.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
10-12
Young Adult
Keywords: Euthanasia; Euthanasia; Euthanasia; Medical ethics; Right to die